China's outward FDI efficiency along the Belt and Road: An application of stochastic frontier gravity model. Issue 3 (5th September 2016) - Fan, Zhaobin; Zhang, Ruohan; Liu, Xiaotong; Pan, Lin
Abstract : Purpose: The purpose of this paper is to estimate the China's outward FDI efficiency and it determinants in 69 countries along the Belt and Road over the period of 2003-2013. Design/methodology/approach: This paper defines the extent of the Belt and Road in terms of geographical boundaries, justifying the application of the stochastic frontier gravity model to the FDI analysis, and then constructing a frontier regression model to assess the China's outward FDI efficiency and it determinants in countries along the Belt and Road. Findings: Regarding the core gravity parameter estimates, China's outward FDI was highly consistent with the gravity model. As far as policy parameters are concerned, China's outward FDI was significantly restricted by some man-made barriers in host countries. According to the estimated FDI efficiency scores, China has huge outward FDI potential in countries along the Belt and Road. In general, China's outward FDI efficiency demonstrated a consistent uptrend from the perspectives of both FDI flows and stocks over the period of 2003-2013. Although China's outward FDI performance indicated a very uneven pattern across different countries and periods, there were no significant performance differences between the Road and Belt. Practical implications: The Belt and Road initiative can be largely beneficial to China's outward FDI, but the specific framework of cooperation should be designed on the basis of determinants of China's outward FDI. The regional cooperation with the Road countries should mainly focus on the removal of business barriers and financial barriers. The regional cooperation with the Belt countries should mainly concern the improvement of local intellectual property protection, the reduction of local tax burden, and removal of business barriers and financial barriers. Originality/value: To the authors' best knowledge, no existing literature has specifically examined the efficiency of China's outward FDI in the countries along the Belt and Road and its determinants.